Application of Tropical Architecture in Convention Hall Design - D D Harisdani; F Kartika (International Journal of Architecture and Urbanism, 2018)
Meeting as one of the daily activities become a base to provide a space which can accommodate communities activities, especially Medan, Indonesia. However, as the number of population increase, especially in the areas with the light of convention hall building, the design of convention hall is required. Building developments that occur at this time in the suburbs of Medan become the basis to create a convention hall. Respond to this problem, a convention hall designed to consider local wisdom in the urban area by applying elements of tropical architecture.